Advanced technologies for improved expression of recombinant proteins in bacteria: perspectives and applications. (1st November 2016) - Gupta, Sanjeev K.; Shukla, Pratyoosh
Abstract: Prokaryotic expression systems are superior in producing valuable recombinant proteins, enzymes and therapeutic products. Conventional microbial technology is evolving gradually and amalgamated with advanced technologies in order to give rise to improved processes for the production of metabolites, recombinant biopharmaceuticals and industrial enzymes. Recently, several novel approaches have been employed in a bacterial expression platform to improve recombinant protein expression. These approaches involve metabolic engineering, use of strong promoters, novel vector elements such as inducers and enhancers, protein tags, secretion signals, high-throughput devices for cloning and process screening as well as fermentation technologies. Advancement of the novel technologies in E. coli systems led to the production of "difficult to express" complex products including small peptides, antibody fragments, few proteins and full-length aglycosylated monoclonal antibodies in considerable large quantity. Wacker's secretion technologies, Pfenex system, inducers, cell-free systems, strain engineering for post-translational modification, such as disulfide bridging and bacterial N-glycosylation, are still under evaluation for the production of complex proteins and peptides in E. coli in an efficient manner. This appraisal provides an impression of expression technologies developed in recent times for enhanced production of heterologous proteins in E. coli which are of foremost importance for diverse applications in microbiology and biopharmaceutical production.